Surface Studies on the Energy Release of the MOST System 2‐Carbethoxy‐3‐Phenyl‐Norbornadiene/Quadricyclane (PENBD/PEQC) on Pt(111) and Ni(111). Issue 25 (23rd March 2023) - Hemauer, Felix; Schwaab, Valentin; Freiberger, Eva Marie; Waleska, Natalie J.; Leng, Andreas; Weiß, Cornelius; Steinhauer, Johann; Düll, Fabian; Bachmann, Philipp; Hirsch, Andreas; Steinrück, Hans‐Peter; Papp, Christian
Abstract: Novel energy‐storage solutions are necessary for the transition from fossil to renewable energy sources. Auspicious candidates are so‐called molecular solar thermal (MOST) systems. In our study, we investigate the surface chemistry of a derivatized norbornadiene/quadricyclane molecule pair. By using suitable push–pull substituents, a bathochromic shift of the absorption onset is achieved, allowing a greater overlap with the solar spectrum. Specifically, the adsorption and thermally induced reactions of 2‐carbethoxy‐3‐phenyl‐norbornadiene/quadricyclane are assessed on Pt(111) and Ni(111) as model catalyst surfaces by synchrotron radiation‐based X‐ray photoelectron spectroscopy (XPS). Comparison of the respective XP spectra enables the distinction of the energy‐rich molecule from its energy‐lean counterpart and allows qualitative information on the adsorption motifs to be derived. Monitoring the quantitative cycloreversion between 140 and 230 K spectroscopically demonstrates the release of the stored energy to be successfully triggered on Pt(111). Heating to above 300 K leads to fragmentation of the molecular framework. On Ni(111), no conversion of the energy‐rich compound takes place. The individual decomposition pathways of the two isomers begin at 160 and 180 K, respectively. Pronounced desorption of almost the entire surface coverage only occurs for the energy‐lean molecule on Ni(111) above 280 K; this suggests weakly bound species. The correlation between adsorption motif and desorption behavior is important for applications of MOST systems in heterogeneously catalyzed processes. Abstract : The molecular solar thermal (MOST) energy storage system 2‐carbethoxy‐3‐phenyl‐norbornadiene/quadricyclane was investigated on Pt(111) and Ni(111) by synchrotron radiation‐based XPS measurements. The in‐situ observation of the adsorption at ∼120 K allowed the distinction of both valence isomers. Temperature‐programmed experiments gave insights into thermally induced reactions and stability boundaries.